Contamination of informally marketed bovine milk with Staphylococcus aureus in urban and peri urban areas of Debre-Zeit, Ethiopia - Desissa, F.; Makita, K.; Teklu, A.; Grace, Delia (Academic Journals, 2012)
A cross-sectional study was conducted from October, 2009 to March, 2010 to assess the level of contamination of informally marketed milk with Staphylococcus aureus at farms and milk collection centers in Debre-Zeit, Ethiopia. One hundred and seventy raw farm bulk milk samples, 25 mixed bulk milk samples and 20 pasteurized and packaged milk samples were collected from 14 milk collection centers and isolation and identification of S. aureus were carried out following standard method. S. aureus was isolated from 44% of farm bulk milk and 72% of milk collection centers’ bulk milk and it was not detected from pasteurized milk samples. Contamination rates of farm bulk milk with S. aureus were significantly different among the collection centers (c2 = 31.8, df = 13, p = 0.003). The milk produced and collected in peri-urban areas was significantly more contaminated with S. aureus (64%) than milk produced and collected in urban areas (38%) (c2 = 7.18, df = 1, p = 0.007). The frequency of isolation of S. aureus in milk collection centers bulk milk varied between 67 and 100% among collection centers. However, the contamination rates were not significantly different among these collection centers (c2 = 1.5, df = 4, p = 0.83). The overall contamination rate at collection centers (72%) was significantly higher than that at the farm level (33%, c2 = 10.6, df = 1, p = 0.001). Overall, the study revealed that milk produced and collected in and around Debre-Zeit was found to be contaminated with S. aureus, raising the issue of quality control and improving the safety of milk to safeguard the consumer from associated health problems and enabling the producers to earn much more from milk sale.